STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN SIKAP PEDULI SOSIAL SISWA DI MADRASAH TSANAWIYAH NEGERI 2 MUARO JAMBI - Muammar Nurkhalis Akmal; Sumirah; Zarfina Yenti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to find out: 1. How is the strategy of Islamic religious education teachers to foster students' social care attitudes at Madrasah Tsanawiyah Negeri 2 Muaro Jambi? 2. What are the inhibiting factors for Islamic religious education teachers in fostering students' social care attitudes at Madrasah Tsanawiyah Negeri 2 Muaro Jambi?. The type of research used in this study is qualitative research. The data collection technique of this research uses observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions and verification. In testing the validity of the data, data triangulation is used. The results of the research are: 1. Teachers' strategies in fostering the social care character of Madrasah Tsanawiyah Negeri 2 Muaro Jambi students, namely: Group work or discussion; instilling religious values through participation in religious activities; Exemplary; Habituation; and Sanction or punishment. 2. Factors that inhibit Islamic Religious Education teachers in fostering students' social care attitudes, namely: Social Media; Entertainment facilities (Games); Student Background; and Community Environment.